2022
DOI: 10.3390/nu14112214
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Supplementation Protects against Nanomaterial-Induced Oxidative Stress and Inflammation Damages: A Meta-Analysis of In Vitro and In Vivo Studies

Abstract: The extensive applications of nanomaterials have increased their toxicities to human health. As a commonly recommended health care product, vitamins have been reported to exert protective roles against nanomaterial-induced oxidative stress and inflammatory responses. However, there have been some controversial conclusions in regards to this field of research. This meta-analysis aimed to comprehensively evaluate the roles and mechanisms of vitamins for cells and animals exposed to nanomaterials. Nineteen studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Vitamin E also mitigated inflammation through decreasing NF-κB while propagating IL-4, and Nrf2 expression levels in rats [ 35 ]. Furthermore, meta-analysis research evaluating in vitro and in vivo evidence emphasized that vitamin E meaningfully diminished oxidative stress (ROS and MDA) as well as markers of inflammation (TNF-α, IL-6, and C-reactive protein) while elevating anti-oxidative markers (GPx) in nanomaterial-induced oxidative stress and inflammation [ 36 ]. Interestingly, we revealed that the effects of piperine and a combination of piperine and exercise training on GSH, TNF-α, and IL-10 levels were significantly greater than vitamin E alone.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E also mitigated inflammation through decreasing NF-κB while propagating IL-4, and Nrf2 expression levels in rats [ 35 ]. Furthermore, meta-analysis research evaluating in vitro and in vivo evidence emphasized that vitamin E meaningfully diminished oxidative stress (ROS and MDA) as well as markers of inflammation (TNF-α, IL-6, and C-reactive protein) while elevating anti-oxidative markers (GPx) in nanomaterial-induced oxidative stress and inflammation [ 36 ]. Interestingly, we revealed that the effects of piperine and a combination of piperine and exercise training on GSH, TNF-α, and IL-10 levels were significantly greater than vitamin E alone.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E supplementation may also be an effective strategy for improving athletic performance and reducing the oxidative stress associated with intense exercise. Vitamin E acts as an antioxidant, reducing oxidative damage to muscle cells and improving immune function and the regulation of lipid metabolism [ 190 ]. Overall, vitamin E supplementation appears to have a beneficial effect on exercise performance by reducing oxidative stress and muscle damage after exercise [ 13 ].…”
Section: The Effect Of Antioxidant Supplementation On Sports Performancementioning
confidence: 99%
“…Bioactive food compounds also include vitamins A [ 60 ], C [ 61 ], and D [ 62 , 63 ] and dietary fiber. Dietary fiber is an element of plant products not digested by human digestive enzymes.…”
Section: Antioxidant Potential Of Bioactive Food Compounds In Obesity...mentioning
confidence: 99%